2017
DOI: 10.1016/j.clinbiochem.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin concentration is positively associated with haemoglobin concentration and inversely associated with albumin to creatinine ratio among Indigenous Australians: eGFR Study

Abstract: Serum bilirubin concentrations were positively associated with Hb and total cholesterol, and inversely associated with ACR. Further research to determine reasons explaining lower bilirubin concentrations among Aboriginal compared with TSI participants are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 37 publications
(27 reference statements)
2
14
0
Order By: Relevance
“…It has been reported that serum bilirubin concentrations are positively correlated with hemoglobin concentration and inversely correlated with ACR among Indigenous Australians [27]. In the current study, we also found that serum bilirubin levels were significantly positively correlated with hemoglobin and albumin levels, and insignificantly inversely correlated with ACR in anti-NMDAR encephalitis.…”
Section: Discussionsupporting
confidence: 74%
“…It has been reported that serum bilirubin concentrations are positively correlated with hemoglobin concentration and inversely correlated with ACR among Indigenous Australians [27]. In the current study, we also found that serum bilirubin levels were significantly positively correlated with hemoglobin and albumin levels, and insignificantly inversely correlated with ACR in anti-NMDAR encephalitis.…”
Section: Discussionsupporting
confidence: 74%
“…J.T. Hughes et al [14] found that serum TB concentration was positively related with TC in 594 Indigenous Australians. Recent reports found the use of statins have a low negative effect on TB concentration [23].…”
Section: Discussionmentioning
confidence: 99%
“…Opposite opinion was also existed. A cross-sectional analysis of 594 Indigenous Australians reported a positive correlation between TB and TC [14]. However, their research population was too small to be demographically representative.…”
Section: Introductionmentioning
confidence: 98%
“…Some recent studies have shown a possible association of elevated concentrations of white blood cells with kidney function decline [5,6] and others have shown that the neutrophil/lymphocyte ratio, a marker of systemic in ammation, may be associated with poor renal outcomes [7,8]. Furthermore, there is also emerging evidence of an association of abnormal liver function tests with decline in eGFR and increasing albuminuria [9] The eGFR study was a longitudinal study of 654 Indigenous Australian adults from more than 20 sites in urban, regional, and remote Australian regions known to have high incidence of dialysis requiring ESKD, and participants were selected across ve strata of health, diabetes status, and kidney function [10][11][12]. This study con rmed the accuracy of the CKD-EPI equation in estimating GFR in Indigenous Australians [12].…”
Section: Introductionmentioning
confidence: 99%
“…In a longitudinal follow-up, progression of CKD occurred rapidly, with loss of kidney function at approximately three times higher rate than expected through healthy ageing [13,14]. Predictors of progression of CKD included elevated baseline urine albumin/creatinine ratio (UACR) and C-reactive protein (CRP) concentrations [9,14,15]. The in ammatory marker, soluble tumour necrosis factor receptor 1 (sTNFR1), was also associated with CKD progression, where this outcome was independent of albuminuria and eGFR in participants with diabetes [4].…”
Section: Introductionmentioning
confidence: 99%